2014
DOI: 10.1111/jsr.12230
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of intervention led by a community pharmacist for improving recognition of sleep apnea in primary care – a cohort study

Abstract: Summary Despite its high prevalence and major public health ramifications, obstructive sleep apnea syndrome (OSAS) remains underdiagnosed. The aim of this study was to determine whether the involvement of a community pharmacist (CP) in the care pathway of a patient at risk of OSAS, through the implementation of a community pharmacist (CP) intervention, was effective, i.e. increased the use of diagnostic tests in this population. We compared a cohort of patients included in a research protocol (exposed to a CP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In France, however, research has been conducted into the cost-effectiveness of a screening strategy in which the GP and community pharmacists collaborated closely. 10 Patients were screened by community pharmacists before visiting their GP. The collaboration was considered to be cost-effective by the researchers and indicated that there is potential in improving the process prior to the final diagnosis, as also corroborated by our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In France, however, research has been conducted into the cost-effectiveness of a screening strategy in which the GP and community pharmacists collaborated closely. 10 Patients were screened by community pharmacists before visiting their GP. The collaboration was considered to be cost-effective by the researchers and indicated that there is potential in improving the process prior to the final diagnosis, as also corroborated by our results.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous OSA cost-effectiveness studies assumed that patients have already received a diagnosis and have been screened. 7,10 Therefore, consequences of years of no treatment until final diagnosis were not taken into account in existing literature. The significance of this study comes with the scarcity of cost-effectiveness studies incorporating effects of OSA screening.…”
mentioning
confidence: 99%
“…Several published studies demonstrate the effectiveness of community pharmacy-based disease screening in promoting early detection and identification of patients at risk of stroke [50], diabetes [51], diabetes and hypertension [52], [53], sleep disorders [54], [55], cardiovascular risk [56], [57], [58], [59] and HIV [60]. A screening programme involving 30 pharmacies and 1,145 participants in Canada showed that an integrated stroke screening programme identified a high prevalence of individuals who could benefit from stroke-prevention therapies [50].…”
Section: Health Screening and Disease Prevention Activitiesmentioning
confidence: 99%
“…Further diagnosis from the referrals provided showed that community pharmacists could raise awareness and assist in initiating behavioural changes in those at risk of developing a sleep disorder [54]. A related study showed that the intervention was associated with higher odds of undergoing a diagnostic test for sleep disorders (adjusted OR: 2.24; 95% CI: 1.25-4.01) [61]. A qualitative study of participants' views of an AF screening service using an electrocardiogram (ECG) app in community pharmacies in Australia suggests that the service is acceptable, easy to use and feasible.…”
Section: Health Screening and Disease Prevention Activitiesmentioning
confidence: 99%
“…The limited evidence has demonstrated the feasibility and effectiveness of CP services. 8,9,11,[14][15][16] It is possible that through the establishment of a screening program for a targeted population, CPs may be able to improve the identification of high risk of OSA among individuals. Interestingly, evidence from the experience of Australians has suggested that pharmacists have been pro-active in extending their roles for providing clinical services associated with OSA.…”
mentioning
confidence: 99%